Screening for tuberculosis and LTBI in diabetes patients, Pohnpei, Federated States of Micronesia - Defang, R. R. (Public Health Action, 2014)
A retrospective cohort study was performed in Pohnpei, a small Pacific Island, to evaluate the feasibility and results of screening adult diabetes (DM) patients for tuberculosis (TB) and latent tuberculous infection (LTBI) using a symptom screen, tuberculin skin testing and chest radiography. Of 79 patients, 65 (82%) completed screening. Two (3%) patients with active TB and 16 (25%) with LTBI were referred for anti-tuberculosis treatment and isoniazid preventive therapy, respectively. It is feasible and worthwhile to screen diabetes patients for TB, but a number of changes are needed to improve both the screening process and the diagnostic yield.